Transformation of the Teaching Process in Learning Population Geography Subjects Through Lesson Study with LOC-R: A Real Action - Hernita Pasongli; Rohana Sufia; Eva Marthinu; Lely Adriani Nasution (JETL (Journal of Education, Teaching and Learning), 2025)
This study explores the effectiveness of integrating Lesson Study with the LOC-R (Literacy, Orientation, Collaboration, Reflection) learning model in teaching Population Geography in higher education—the research aimed to enhance student literacy, learning activity, and the overall teaching process. A classroom action research approach was employed, incorporating two cycles of Lesson Study with LOC-R implementation. Data was collected through observations, interviews, and document analysis. The findings reveal that the combined model significantly improved student literacy, particularly in data interpretation and understanding. It also fostered active student participation, collaboration, and critical thinking skills. The Lesson Study cycles provided a platform for teacher professional development, leading to improved teaching practices and a more collaborative learning environment. This research suggests that integrating Lesson Study with LOC-R offers a promising approach to enhancing Population Geography teaching and learning. Further studies are recommended to explore the application of this model in other disciplines and contexts.